A Analysis of Land Use on Water Quality in Merjosari Village, Lowokwaru Subdistrict, Malang City - K, Maharani Pertiwi; Anshary, Muhammad Reza; Kartikaningsih, Hartati; Fadila, Rizki (Gema Lingkungan Kesehatan, 2025)
Malang City faces several environmental challenges, including inadequate sanitation and water management, which have not been fully addressed across all aspects of life. This is not in line with the Sustainable Development Goals, which aim to ensure the availability and sustainable management of clean water and sanitation for all people. Malang City is also experiencing increasingly massive land use changes, from green open land to housing, which can impact clean water quality. This study aims to assess the quality of clean water from the non-Local Water Supply Utility in Merjosari Village, Lowokwaru Subdistrict, Malang City, which is undergoing land-use transformation. A quantitative observational approach was employed using the National Sanitation Foundation's Water Quality Index (NSF-WQI) method, which evaluates water quality based on physical, chemical, and biological parameters. The results showed that the water quality index in Merjosari Village, Lowokwaru District, Malang City, analyzed using the NSP-WQI method, has a value of 77.53 and falls within the good criteria. However, several parameter values exceed the clean water standard. The average value of the DO parameter, at 5.85 mg/,L is less than the quality standard of 6 mg/L. The average value of the BOD parameter, at 8.12 mg/,L exceeds the quality standard of 2 mg/L. The pH parameter at several sample points exceeds the quality standard of above 8.5, and the Nitrate Parameter at several sample points exceeds the quality standard of 20 mg/L. In conclusion, the land cover change in the Merjosari area, Lowokwaru District, Malang City, does not significantly affect the quality of clean water. However, the values of several water parameters exceed the clean water standard, which has the potential to impact public health negatively.